FIRST DISCOVERY OF MIDDLE TOURNAISIAN CONODONTS IN THE GRIOTTE-TYPE NODULAR PELAGIC LIMESTONES, ISTANBUL AREA, NW TURKEY (Rivista italiana di Paleontologia e Stratigrafia, 2004)
The uppermost layers of the Ayineburnu member of the Büyükada Formation in the Istanbul-Gebze area are represented by Griotte-type pelagic nodular limestones. They yielded conodont elements (Bispathodus stabilis and Siphonodella lobata) that can identify the interval from the upper part of the sandbergi Zone through the isosticha- Upper crenulata Zone - middle Tournaisian - Early Carboniferous. This is the first middle Tournaisian conodont record published from an autochthonous succession in the Istanbul Terrane, NW Turkey. This level characterizes the very last carbonate deposition and is followed by lydites and black siliceous shales and finally by the accumulation of flysch-type deposits during the late Tournaisian and early Visean, that mark the onset of Variscan events to the north of the Istanbul Terrane. A correlation with the Lower Carboniferous successions in the easterly-located Zonguldak area suggests that Istanbul and Zonguldak terranes were in quite different palaeogeographic positions during this time interval.